The U-shaped association between initial serum phosphate level and mortality of traumatic brain injury patients - Ruoran Wang; Xin Yang; Jianguo Xu; Min He (Frontiers in Neurology)
BackgroundPhosphate disorders, including hypophosphatemia and hyperphosphatemia, influence the prognosis of patients. We designed this study to explore the relationship between serum phosphate levels and mortality in traumatic brain injury (TBI) patients.MethodsTBI patients from the Medical Information Mart for Intensive Care-III (MIMIC-III) database were included in this study. Univariate logistic regression analysis was conducted to identify potential risk factors for TBI mortality. Restricted cubic spline (RCS) analysis was conducted to explore the non-linear relationship between serum phosphate level and TBI mortality, both before and after adjusting for risk factors identified in the univariate logistic regression analysis. Length of ICU stay, length of hospital stay, and 30-day mortality were compared between groups with different serum phosphate levels.ResultsA total of 400 TBI patients died, resulting in an overall mortality rate of 17.6%. Utilizing the RCS analysis, both unadjusted and adjusted associations between serum phosphate levels and TBI mortality were shown as a U-shaped curve. We divided the serum phosphate levels into three groups: < 3.0, 3.0–4.0, and >4.0 mg/dl, according to the U-shaped curve. The multivariate logistic regression analysis revealed that levels < 3.0 mg/dl (p = 0.012) and >4.0 mg/dl (p = 0.024) were associated with a higher risk of mortality than 3.0–4.0 mg/dl. Mortality rates in these three groups were 19.1%, 14.4%, and 23.4%, respectively (p < 0.001). Kaplan–Meier analysis showed a significant difference in survival among the three groups (p < 0.001).ConclusionBoth higher and lower serum phosphate levels are associated with increased mortality in TBI patients. Evaluating serum phosphate levels is beneficial to identify TBI patients at high risk for poor prognosis.